EVALUASI PROGRAM LATIHAN ASOSIASI SEPAKBOLA KOTA MATARAM - Bausad, Andi Anshari; Musrifin, Arif Yanuar; Akhmad, Noor (Jurnal Ilmiah Mandala Education (JIME), 2022)
Optimal sports achievement can be achieved with good and correct coaching as a whole. The sport of football is not included in the 16 sports that are currently carrying out PUSLATDA, because the 2018 PORPROV event did not perform well. The training program that has been prepared and run by the Mataram City soccer coach, it is necessary to evaluate the preparation of the Mataram City soccer athlete training program. Where one of the main elements in the preparation of the training program is to improve the physical condition of the Mataram City football players. The formulation of the problem that will be raised in this study referring to the background description is (1) How is the achievement of planning the Mataram city association football training program in 2021? (2) What is the physical condition of the Mataram city soccer athletes in 2021?. The objectives of this research to be achieved are (1) to identify the implementation of the training program carried out by the trainers in the field. (2) Measuring the physical condition of the Mataram city soccer athletes. The research method used is quantitative and qualitative (mix method). The subjects of this study were the head coach of football in the city of Mataram and football athletes in the city of Mataram. The place of research was carried out at the PSSI office in Mataram City, the football training ground of GOR Turide Mataram, and measurements of physical condition in the sports laboratory of FIKKM UNDIKMA.The test instrument to measure the design of the preparation of the training program uses the Test Instrument for the Evaluation of the Training Program Arranged by the Trainer. To measure the physical condition of the instrument used, there are 7 test items in table 3.1. Descriptive and inferential statistical analysis techniques such as mean (average), standard deviation (standard deviation), variance, maximum and minimum values. In this study, probability statistics are used to find the percentage of each answer on each item and then the average of the overall scores using SPSS version 23 is calculated. The results of the study, 1. Measurement of the dominant physical condition test that has been carried out for each test item from 30 soccer athletes Mataram city ball in the average percentage is in good condition, with 22 athletes getting good category out of a total of 30 athletes. 2. The percentage of the results of the evaluation of the training program evaluation indicator will get 64% which means that the overall training program for the Mataram City Soccer athletes is said to be "STRONG.